Analysis of the Regret Speech Act in Japanese - Amalia, Azila Dinda; Haristiani, Nuria (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2022)
The characters in Japanese animation (or anime) are the center of this study, which examines the ways in which they demonstrate regret. Many prior studies have used anime as research study material because it is one of the media that is extremely interesting to analyze from a variety of perspectives. For this analysis, researchers used information from 14 episodes of the 24-minute-long anime series Golden Time. The animation depicts the daily lives of Japanese college students, and the numerous struggles they endure are depicted through several expressions of regret. The data gathered is derived from transcripts of talks carried out by the anime characters and is utilized as research material. The collected data was 54 regret speech act utterances and then examined using a qualitative descriptive approach. The data were then classified into the varieties of regret indicated by Pink. After being analyzed, it was shown that noni form dominates the regret speech acts performed in anime, and the types of regret speech acts that are commonly employed are those related to regret of an action or opportunity that should have been taken by someone. It is also known in this study that Japanese people tend to express regret by providing information about facts that differ from what they expected, causing them to feel regret. When they express regret, they may also blame themselves for their actions.